Collision Attacks on Reduced RIPEMD-128 - Zhengrong Lu; Hongbo Yu; Xiaoen Lin; Sitong Yuan (IACR Transactions on Symmetric Cryptology)
RIPEMD-128 is an ISO/IEC standard hash function based on a doublebranch Merkle-Damgård structure. Its compression function includes two branches with distinct Boolean functions and message expansion permutations. To perform a collision attack, differential characteristics must be constructed simultaneously for both branches under the same message word difference, and the message modification order must align with conditions in both branches. These factors make collision attacks on (reduced) RIPEMD-128 highly challenging. In 2014, an attack on 40 steps of RIPEMD-128 was achieved by Wang with no state differences in round 3. In this work, we analyze message permutation properties and propose two new structures for creating message differences. These structures enable high-probability local collisions in both branches of round 3, extending the attack to more steps. Notably, the second structure can eliminate all state differences in round 3, allowing the attack to cover more than three whole rounds. To ensure practical attacks, we limit the number of conditions based on our message modification strategy and use multi-step message modification techniques to control more conditions. As a result, we successfully generate colliding message pairs for 46-step and 54-step reduced RIPEMD-128, with time complexities of approximately 242 and 254, respectively.